Obrabna odpornost konstrukcijskega jekla, nitriranega v plazmi - Podgornik, Bojan (Strojniški vestnik, 2001)
In our study wear resistance of plasma and pulse plasma nitrided 42CrMo4 steel was evaluated under lubricated sliding and pitting wear conditions, where hardened samples were used as a reference. The nitrided samples were characterised using metallography, microhardness, residual stress and surface examination techniques. After surface treatment, lubricated sliding wear tests were performed on a pin-on-disc machine in which surface treated pins were loaded against hardened ball bearing steel discs. Pitting wear tests were performed on back-to-back gear test rig. Experimental results indicate, that the wear resistance of 42CrMo4 steel, especially pitting wear resistance can be greatly improved by means of plasma and pulse plasma nitriding. However, plasma and pulse plasma nitrided 42CrMo4 steel showed very similar sliding and pitting wear resiostance.
Keywords: nitriranje plazemsko; nitriranje plazemsko pulzno; jamičenje; drsenje; obraba; konstrukcijska jekla; nitriranje; preiskava materiala